General Systems Theory in the Dialogue between Peasant Knowledge from the Colombian Altiplano Cundiboyacense and Climatology/Edaphology - Lamprea Quiroga, Pedro Simón; Sanabria Marin, Rigaud (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article discusses criteria, categories, and strategies of edaphology and climatology for constructing traditional and scientific knowledge, which are contrasted for raindrop erosion in the Bogotá-Duitama corridor of the Altiplano Cundiboyacense, Colombia. The analysis applies tools of general systems theory to facilitate the integration of scientific explanations by dialoguing with and comprehending peasant communities. In incorporating the cultural variables of peasant wisdom into scientific knowledge, we can understand and complement the relationships involved in soil erosion due to rainfall, unlike climate change and variability represented by altered rainfall patterns and extreme temperatures. The systemic analysis of this knowledge increases the synergy between the qualitative and quantitative approaches; therefore, they become a useful tool for mixed approach analysis.